Education About The Importance of Nutritious Food For Pulmonary TB Sufferers at Tanjung Morawa Health Center - Gurusinga, Rahmad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2023)
Tuberculosis (TB) is one of the diseases that can affect changes in appetite, when the condition of TB sufferers is dying then the body cannot absorb nutrients from food perfectly so that nutritional needs are very less if not balanced with nutritious foods. In addition, TB sufferers also often experience nausea and even vomiting and often also experience cramps in the stomach due to side effects of the drugs they take. Therefore, TB sufferers are very important to be able to apply healthy and nutritious habits or diets in order to speed up the healing process. The purpose of this education is to be able to increase the knowledge and understanding of TB sufferers in choosing healthy and nutritious foods. The method used was a pretest before the presentation of the material, then continued with an explanation or presentation of material about the importance of nutritious food, after that the posttest was again carried out, the study was carried out at the Tanjung Morawa Health Center, Deli Serdang Regency with a total of 21 participants. From the results of the activity before education was carried out about the importance of nutritious food, the majority of participants were less knowledgeable and after education, the majority were well informed and participants also understood that healthy and nutritious food does not have to be expensive, but nutritious food is also a lot of types of food at affordable prices. It was concluded that it is important to do education or explanation with nutritious food so that people can apply it in their daily lives until they are declared cured by a doctor.